Impact of filtering methods on ultrafine particles turbulent fluxes by eddy covariance. (15th September 2022) - Pappaccogli, Gianluca; Famulari, Daniela; Donateo, Antonio
Abstract: In the present work, a comparison between Linear Detrending (LDT) and a Recursive Digital Filter (RDF) in removing the low-frequency contribution to the vertical turbulent fluxes was performed. The two methods were applied in order to obtain a correct evaluation of ultrafine particles, sensible heat and momentum turbulent fluxes. Exchange velocity was also evaluated separating the positive cases (the so called deposition velocity V d ) from negative cases (named emission velocity V e ). The low-frequency time scales (τc ) required by the RDF were obtained by means of an ogive analysis of turbulent fluxes for different atmospheric stability conditions (i.e. unstable, stable and neutral). RDF was applied also with a constant low-frequency time scale (RDF300, τc  = 300s). The stationarity test proposed by Mahrt (1998 - MST98) has been applied to momentum, kinematic temperature and particle number fluxes before and after applying LDT and RDF methods, in order to investigate the impact of filtering criteria on stationarity of time series. Results emphasised that there were no significant differences in stationary cases for different filtering procedures. The comparison analysis on the main turbulent variables highlighted that wider discrepancies occurred between LDT and RDF300, showing on average an increase in turbulent number particles flux obtained through RDF methods, especially in unstable atmospheric conditions. On the other hand, a mean decrease for momentum and sensible heat fluxes was observed. Filtering procedures led to a slight increase of exchange velocity, although an underestimation occurred for emission and deposition velocities when considered separately. Graphical abstract: Image 1 Highlights: The performance of Linear Detrending and a Recursive Filter (RF) is investigated The time scales required by the RF were obtained through an ogive analysis An increase in turbulent number particles flux was obtained through RF A mean decrease for momentum and sensible heat fluxes was observed applying RF RF increases the exchange velocity while decreasing the emission/deposition one